Diversity of physic nut (Jatropha curcas) in Malaysia: Application of DIVA-geographic information system and cluster analysis. - Shabanimofrad, Mahmoodreza; Yusop, Mohd Rafii; Saad, Mohd Said; Megat Wahab, Puteri Edaroyati; Biabanikhanehkahdani, Alireza; Latif , M.A. (Southern Cross Publishing, 2011)
A sum of 59 accessions of physic nut, Jatropha curas were collected from different locations of Selangor, Kelantan and Terengganu states of Malaysia to assess genetic diversity using multivariate analysis and DIVA-geographic information system (GIS). Six quantitative characters, seed length, seed width, fruit length, fruit width, 100 seed weight and oil content were recorded. Based on 6 quantitative characters, 59 accessions were grouped into three clusters at a coefficient level of 3.7. Highly positive correlations were found between fruit length and fruit width, fruit length and seed length, fruit width and seed length, fruit length and seed width, fruit width and seed width and seed length and seed width. DIVA-GIS showed the highest diversity index for 100 seed weight in the J. curcas accessions which were collected from the central parts of Selangor state. On the other hand, the highest diversity index for oil content was observed in the accessions of northern parts and costal region of Terengganu state, followed by the central parts of Selangor state in Malaysia.